2005
DOI: 10.1073/pnas.0504663102
|View full text |Cite
|
Sign up to set email alerts
|

Role of the WASP family proteins for Mycobacterium marinum actin tail formation

Abstract: Mycobacterium marinum, a natural pathogen of fish and frogs and an occasional pathogen of humans, is capable of inducing actin tail formation within the cytoplasm of macrophages, leading to actinbased motility and intercellular spread. Actin tail formation by M. marinum is markedly reduced in macrophages deficient in the Wiskott-Aldrich syndrome protein (WASP), which still contain the closely related and ubiquitously expressed protein N-WASP (neuronal WASP). In fibroblasts lacking both WASP and N-WASP, M. mari… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
48
0

Year Published

2006
2006
2023
2023

Publication Types

Select...
3
3
2

Relationship

1
7

Authors

Journals

citations
Cited by 59 publications
(53 citation statements)
references
References 43 publications
5
48
0
Order By: Relevance
“…Furthermore, both WASP and N-WASP were activated during phagocytosis in a Cdc42-dependent manner ( Figure 5, B and C). N-WASP is a ubiquitously expressed homologue of WASP that is expressed in macrophages in addition to WASP (Stamm et al, 2005). A role for N-WASP in the internalization of pathogens in nonhematopoietic cells has been reported recently (McGee et al, 2001;Bierne et al, 2005).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, both WASP and N-WASP were activated during phagocytosis in a Cdc42-dependent manner ( Figure 5, B and C). N-WASP is a ubiquitously expressed homologue of WASP that is expressed in macrophages in addition to WASP (Stamm et al, 2005). A role for N-WASP in the internalization of pathogens in nonhematopoietic cells has been reported recently (McGee et al, 2001;Bierne et al, 2005).…”
Section: Discussionmentioning
confidence: 99%
“…Consistent with results reported using human monocyte-derived macrophages (Lorenzi et al, 2000), BMMs from WASP-deficient mice showed a 50% decrease in phagocytosis ( Figure 3A). The residual phagocytosis observed in the absence of WASP may be due to the presence of N-WASP in macrophages (O'Sullivan et al, 1999;Stamm et al, 2005). To address the role of this WASP homologue, the phagocytic ability of cells in the presence of wiskostatin was assessed.…”
Section: Wasp/n-wasp Potential Effectors Of Cdc42mentioning
confidence: 99%
“…The actin polymerization system Arp2/3 complex has been manipulated by several pathogens differently. Some mimics the Wiskott-Aldrich syndrome protein (WASP) family [56], while other's recruit WASP directly to activate Arp2/3 [57]. Examples of the first include the actA protein of listeria and RickA of riquetsia.…”
Section: Acting On Actin For Pathogen Dissemination: Actin-based Motimentioning
confidence: 99%
“…Examples of the first include the actA protein of listeria and RickA of riquetsia. For the second examples exist as is the case of IcsA of S. flexneri and nondetermined factors of M. marinum but dependent on the ESAT-6 secretion system 1 [57]. M. marinum is a water-borne bacterium that naturally infects fish and amphibians and is an opportunistic pathogen for humans causing tuberculosis while Rickettsia conorii belongs to the spotted fever group of Rickettsia species transmitted by ticks [55].…”
Section: Acting On Actin For Pathogen Dissemination: Actin-based Motimentioning
confidence: 99%
“…However, recent reports have indicated that free M. tuberculosis, Mycobacterium marinum, and Mycobacterium leprae can be present in the cytoplasm (27,28,30) and demonstrated that intracellular M. marinum not only enters the cytoplasm of infected macrophages but also has the ability to be propelled by actin-based motility (27,28), as observed for numerous intracellular pathogens, including Listeria monocytogenes, Shigella flexneri, and Rickettsia rickettsii (11,27,28,29). Upon cell invasion, mycobacteria may thus be in contact with cytosolic components, including actin, which may be involved in epithelial cell trafficking.…”
mentioning
confidence: 99%